The effect of single-tasks and dual-tasks on balance in older adults - Sertel, Meral (Cogent social sciences, 2017)
Purpose: This study has been planned to show how the balance is influenced when additional cognitive and motor tasks are given to older people. Methods: 159 older adults (61 Females/98 Males) between 65 and 80 years of age were included in the study. The single and dual task performances of the individuals were evaluated with the Stand on One Foot Test, Time up and Go Test (TUG), and Sit Down-Stand up Test; and the cognitive status was evaluated with the Mini Mental Status Test. The individuals were asked to transfer an object from one hand to the other as an additional motor task during the balance tests; and were asked to count by twos as a cognitive additional task. Results: When the taskless balance performances of the individuals and their dynamic balances during the additional cognitive and motor tasks were compared, it was observed that the duration of completing the test increased at a statistically significant level when both motor and cognitive additional tasks were added in TUG (p < 0.001); and in Sit down-Stand up, Stand on One Foot Tests (right and left), on the other hand, it was observed that the durations of the tests decreased when both additional motor and cognitive tasks were given (p < 0.001). Conclusion: At the end of our study, we observed that the additional tasks given to the older adults decreased the balance performance. We consider that balance trainings must be given together with motor and cognitive tasks to older people.